2020
DOI: 10.1097/md.0000000000023557
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic nomogram incorporating red cell distribution width for patients with intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is the second most common subtype of stroke with higher mortality and morbidity, and it lacks effective prognostic markers. The aim of this research is to construct newly valuable prognostic nomogram incorporating red blood cell distribution width (RDW) for ICH patients. We retrospectively analyzed 953 adult patients with ICH. The impacts of RDW on short-term mortality and functional prognosis were calculated using Akaike information criterion (AIC), Bayesian informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…The GCS score is the most widely used indicator for assessing the degree of coma in patients, and lower GCS scores are associated with a higher risk of death ( Saika et al, 2015 ; Widyadharma et al, 2021 ). Consistent with our results, many nomogram-based studies have reported that a decrease in GCS scores significantly contributes to an increase in mortality and the likelihood of hematoma expansion in ICH patients ( Yao et al, 2015 ; Cui et al, 2020 ; Chen et al, 2021 ; Kang et al, 2021 ). The bleeding volume increases upon rupture of vessels and can continue to increase after ICH is diagnosed by imaging, and, consequently, the baseline bleeding volume and hematoma enlargement are strongly associated with poor clinical outcomes ( Al-Shahi Salman et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The GCS score is the most widely used indicator for assessing the degree of coma in patients, and lower GCS scores are associated with a higher risk of death ( Saika et al, 2015 ; Widyadharma et al, 2021 ). Consistent with our results, many nomogram-based studies have reported that a decrease in GCS scores significantly contributes to an increase in mortality and the likelihood of hematoma expansion in ICH patients ( Yao et al, 2015 ; Cui et al, 2020 ; Chen et al, 2021 ; Kang et al, 2021 ). The bleeding volume increases upon rupture of vessels and can continue to increase after ICH is diagnosed by imaging, and, consequently, the baseline bleeding volume and hematoma enlargement are strongly associated with poor clinical outcomes ( Al-Shahi Salman et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to many previous studies, we found that age ( Inoue et al, 2018 ; He et al, 2020 ), GCS score ( Cui et al, 2020 ), and bleeding volume ( Al-Shahi Salman et al, 2018 ; Du et al, 2020 ; He et al, 2020 ; Kang et al, 2021 ; Masotti et al, 2021 ; Pasi et al, 2021 ) were independent risk factors for the poor prognosis of ICH patients. It is generally believed that the main causes of ICH are hypertension and CAA ( Schrag and Kirshner, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…In regard to Hb levels, lower mean admission values were recorded in the unfavorable outcome group, without statistical significance or without meeting the criteria of the definition of anemia ( 39 ). RDW is another inexpensive automatically generated hematology parameter that is impacted by inflammation ( 29 ), and our results indicated a modest correlation with admission PHE, but this was not associated with day 90 FO.…”
Section: Discussionmentioning
confidence: 60%
“…ICH induces a state of systemic and peripheral inflammation, thus increasing circulating WBC and recruiting certain molecules within the affected area, which amplifies local damage (13,22). Previous studies have reported results for several inflammatory biomarkers and calculated indexes (Hb, absolute RDW, GRA, LYM, PLT, NLR, PLR) that contribute to the existing data on FO prognostication (5,6,17,19,28,29,46,47), but the cohort assessed in the present study did not display statistically significant results, only in-line tendencies with previously published evidence. Furthermore, moderate negative correlations were determined between WBC, GRA, SII and PHE growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation